2023
DOI: 10.3390/photonics10020161
|View full text |Cite
|
Sign up to set email alerts
|

The Progress and Trend of Heterogeneous Integration Silicon/III-V Semiconductor Optical Amplifiers

Abstract: Silicon photonics is a revolutionary technology in the integrated photonics field which has experienced rapid development over the past several decades. High-quality III-V semiconductor components on Si platforms have shown their great potential to realize on-chip light-emitting sources for Si photonics with low-cost and high-density integration. In this review, we will focus on semiconductor optical amplifiers (SOAs), which have received considerable interest in diverse photonic applications. SOAs have demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The demonstrated proof-of-concept devices still have certain challenges, such as the alignment of the metasurface chip on top of a silicon waveguide chip. A practical solution for a compact device is to use flip-chip bonding and transfer printing techniques, 38 or as the most compact solution, to fabricate the reflective metasurface directly on the horizontal surface of the URM. Further, to implement a device that is more useful from the application point of view, such as PR serving as a Pauli-Z gate for quantum computing, 39 more advanced designs are needed in which different waveguides are used as input and output, e.g., a Michelson interferometer based on a 50:50 splitter.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated proof-of-concept devices still have certain challenges, such as the alignment of the metasurface chip on top of a silicon waveguide chip. A practical solution for a compact device is to use flip-chip bonding and transfer printing techniques, 38 or as the most compact solution, to fabricate the reflective metasurface directly on the horizontal surface of the URM. Further, to implement a device that is more useful from the application point of view, such as PR serving as a Pauli-Z gate for quantum computing, 39 more advanced designs are needed in which different waveguides are used as input and output, e.g., a Michelson interferometer based on a 50:50 splitter.…”
Section: Discussionmentioning
confidence: 99%
“…The main consideration when proposing a DSORN as the major communications platform is regarding the ability of supporting devices in FSO such as an optical amplifier. The capability of an optical amplifier to boost a signal strength right now is available and also reaching an advanced stage of development [173,174]. An optical amplifier that has a high power output is the first requirement to transmit an optical propagation thousands of kilometers away from the geo-stationary orbit of Earth.…”
Section: Space Optical Satellite Communicationsmentioning
confidence: 99%
“…[15][16][17][18] A review of various hybrid integration technologies can be found in. [19][20][21][22] This paper describes the wafer reconstitution process flow of InGaAs/InP tiles on 200 mm silicon substrates and the impact of this integration on diode device performance. The integration scheme uses a template Si pocket wafer for III-V die placement on a temporary carrier with glue.…”
Section: Introductionmentioning
confidence: 99%